Conflict Management Style and Employee Performance: Leadership and Emotional Intelligence as Moderation - Wardana, I Made Aditya; Sri Asih, Anak Agung Ketut; Ardani, Wayan; Aristana, I Nengah (Jurnal Ilmiah Sumber Daya Manusia, 2023)
Increasing competition forces all businesses to develop. These demands often lead to a conflict which will later have an impact on the performance of employees, especially SMEs. Therefore, conflict management is needed so that the stability of the situation can be maintained. The purpose of this study was to analyze and explain the effect of conflict management style on employee performance, and to determine the role of leadership and emotional intelligence as moderating variables. This research involved UKM employees in regencies/cities in Bali. Data collection uses a questionnaire with the snowball method, the questionnaire is distributed electronically using the Google form. The data used were 174 respondents and then analyzed using the Smart PLS application. The findings of this study indicate that the style of conflict management has a significant effect on the performance of SMEs. Leadership shows a moderating role with a tendency to reduce the interaction of conflict management styles on performance. Meanwhile, emotional intelligence acts as a full moderator of the influence of conflict management styles on the performance of SME employees.